Acusações contra moradores da Capitania do Ceará elencadas nos Índices dos Cadernos do Promotor da Inquisição de Lisboa (1720 – 1765) (Revista de História Regional, 2022)
The Lisbon Inquisition’s Cadernos do Promotor contain numerous accusations against residents of Ceará. These documents, rich in information about the 18th century, especially regarding private life, are available digitally on the National Archives of Torre do Tombo's website, but have rarely been explored by historians. I intend to demonstrate that researchers can locate complaints with relative accuracy from the different indices prepared by the Inquisition's agents. As a resource for historians who research the colonial period, I prepared a table with the complaints referring to residents who lived in the Captaincy, indicating the accused, their guilt, places where they lived, and the Cadernos and folios in which the accusations can be found.. This instrument will enable historians to develop more in-depth analyzes of the complaints listed. Throughout this research, it was possible to conclude that the accusations against the inhabitants of Ceará mainly involved cases of heresy, contempt, and bigamy.